Digital Banks in Indonesia: Potential and Problems - Sopamena, Ronald Fadly; Abubakar, Lastuti; Handayani, Tri (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Digital Bank based on POJK No.12/POJK.03/2021 Concerning Commercial Banks, is a bank incorporated in Indonesia that provides and carries out business activities mainly through electronic channels without a physical office other than the head office or using limited physical offices. Digital banks are then explained in Article 7B and Article 20A of the PPSK Law stating that both commercial banks and Islamic commercial banks can operate as digital banks. Based on this, the business fields of digital banks are the same as the business fields of commercial banks or Islamic commercial banks. Digital banks are divided into digital banks that are subsidiaries of conventional banks and banks that have been purely digital banks since their inception.Purposes of the Research: Examine the potential of digital banks in supporting the economy and discuss the legal issues faced by digital banks.Methods of the Research: This writing uses a normative legal research method with a statutory approach and a conceptual approach.Results Main Findings of the Research: The results of the study show that in the current era of globalization where technology is not something that is difficult to access, digital banks are here to bring a breath of fresh air to the banking world. Customers will get instant services without having to come directly to the office to get 24-hour banking services. Digital banks have one problem, namely credit distribution carried out through applications or websites which causes credit analysis with the 5C method to not run optimally so that it will increase the ratio of non-performing loans or NPLs. Therefore, digital banks need to prepare a Bank Credit Policy (KPB) that accommodates digital bank credit distribution as part of digital bank risk management as mandated in Article 2 Number 1 of the Financial Services Authority Regulation Number 18/POJK.03/2016 concerning the Implementation of Risk Management for Commercial Banks. The policy must be able to make digital banks able to conduct credit analysis without sacrificing the principle of prudence. The policy can be in the form of a loan limit, tenor or examination of additional documents required so that there is no non-performing loan in the future.